The Mediation Model of Organizational Commitment on the Effect of Job Characteristics on Organizational Citizenship Behavior among Generation Z Employees in Makassar City - Andi Rinda Oktariani; AR Hidayat; Wandi Janwar; Gary Leonard Hendrik (At-Tadbir : jurnal ilmiah manajemen, 2026)
For organizations employing Generation Z workers, designing meaningful, feedback-rich, and skill enhancing jobs can strengthen organizational commitment and promote voluntary extra-role behavior. Managers should prioritize job design and employee engagement programs to foster higher OCB levels and organizational effectiveness.. This study aims to examine the effect of job characteristics on Organizational Citizenship Behavior (OCB) among Generation Z employees in Makassar City, as well as the mediating role of organizational commitment in this relationship. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM.. Data were collected through purposive sampling from 120 Generation Z employees. The results indicate that job characteristics positively and significantly influence both organizational commitment and OCB. Organizational commitment also has a positive and significant effect on OCB. Furthermore, organizational commitment partially mediates the relationship between job characteristics and OCB, although the magnitude of mediation is relatively weak. The model demonstrates substantial predictive power for OCB and moderate predictive power for organizational commitment.